Relationship between the stroke mechanism of symptomatic middle cerebral artery atherosclerotic diseases and culprit plaques based on high-resolution vessel wall imaging - Lin, Guo-hui; Song, Jian-xun; Huang, Teng-da; Fu, Nian-xia; Zhong, Li-ling (Frontiers in Neurology, 2022)
Purpose For patients with symptomatic middle cerebral artery (MCA) atherosclerotic stenosis, identifying the potential stroke mechanisms may contribute to secondary prevention. Our aim was to determine the mechanism classification of large artery atherosclerosis stroke based on conventional neuroimaging of symptomatic MCA atherosclerotic stenosis and to explore the relationship between different stroke mechanisms and culprit plaque based on high-resolution vessel wall imaging (HR-VWI). Methods We recruited 61 patients with acute ischaemic stroke due to MCA atherosclerotic stenosis from Shenzhen Bao'an District People's Hospital. According to the prespecified criteria based on infarct topography and magnetic resonance angiography, the two researchers independently divided the possible stroke mechanisms into perforator artery occlusion (P), artery-to-artery embolism (A), hypoperfusion (H), and mixed mechanisms (M). The correlation between the characteristics of MCA M1 culprit plaque and different stroke mechanisms was analysed based on HR-VWI. The indicators included the plaque surface irregularity, T1 hyperintensity, location, plaque burden, remodelling index, enhancement rate and stenosis rate. Results We found that perforator artery occlusion was the most common mechanism (37.7%). The proposed criteria showed a substantial to excellent interrater reproducibility (κ, 0.728; 0.593-0.863). Compared with the P group, the surface irregularity, T1 hyperintensity and obvious enhancement of the culprit plaque in the A group were more common (p < 0.0125). Compared with the other stroke mechanisms, positive remodelling of culprit plaques was more common (p < 0.0125), the RI was greater (p<0.05) and the PB was the smallest (p<0.05) in the P group. In addition, the ER was smaller in the P group (p<0.05). Compared with the A group, T1 hyperintensity of the culprit plaque was more common in the H group (P < 0.0125), and the stenosis rate was greater (p<0.05). Conclusion It is feasible to evaluate the culprit plaque characteristics of symptomatic MCA atherosclerotic patients in different stroke mechanisms based on HR-VWI. There is a trend that the culprit plaques of the artery-to-artery embolic mechanism show irregular surfaces and obvious enhancement. The culprit plaques in the perforator artery occlusion mechanism are more commonly associated with PR and mild PB, while T1 hyperintensity is more common with the hypoperfusion mechanism.